Clinical Profile of Non-thyroidal Cancer Patients with Tyrosine Kinase Inhibitor-Induced Thyroid Dysfunction in the University of Santo Tomas Hospital, Philippines: A 5-Year Single-Center Retrospective Study - Luna, Nenuel Angelo; Quinitio, Jennilyn; Mendoza, Erick; Kho, Sjoberg; Caguioa, Priscilla (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Objectives. This study aimed to determine the clinical profile of non-thyroidal cancer patients with thyroid dysfunction associated with tyrosine kinase inhibitor (TKI) therapy at the University of Santo Tomas Hospital (USTH), Philippines. Methodology. This is a retrospective observational study of TKI-initiated adult non-thyroidal cancer patients with thyroid function testing from 2013 to 2018. Results. Forty percent (95% CI: 26.2% - 58.61%) of the sixty individuals who had thyroid function tests (TFT) had incident thyroid dysfunction. Thirty percent had hypothyroidism (i.e., 25% overt [mean TSH 16.64 uIU/mL]; 5% subclinical [mean TSH 6.62 uIU/mL]). The median time at risk was 8 and 16 months for overt and subclinical hypothyroidism, respectively. Fifty-six percent had persistent hypothyroidism (median TSH 16.75, p = 0.009). The average time to recovery of transient hypothyroidism was 39 months. Ten percent had hyperthyroidism with a median time at risk of 1.5 months. Non-small cell lung cancer and renal cell carcinoma were possible associated risk factors of thyroid dysfunction. Conclusion. TKI-induced thyroid dysfunctions are common. Screening and monitoring for thyroid abnormalities during TKI therapy is important.